Histopathological and immunohistochemical investigation of mammary tumors in female cats in Northeast Algeria - Zahra Gabli; Zouhir Djerrou; Leila Beddar (Біологія тварин)
Cancer is a leading cause of feline mortality globally. This study focuses on delineating mammary gland tumor prevalence and anatomopathological characteristics in cats from northeastern Algeria. Encompassing the period from January 2021 to March 2022, the research included 50 cats from Constantine and Annaba provinces, revealing an overall 20% feline mammary tumors (FMT) prevalence. Siamese cats exhibited a higher rate compared to crossbred cats, with a mean age of positively diagnosed cats at 9±0.3 years. Histopathological classification identified 20% of tumors as malignant, specifically squamous cell carcinoma, cribriform carcinoma, and comedocarcinoma. In conclusion, further epidemiological investigations are essential to understand the risk factors in the initiation and progression of these health issues. In contrast to canine species, FMTs are less diverse, predominantly simple malignant tumors. Benign FMTs are infrequent, and the existence of complex and mixed tumors in felines remains unclear. This study selected three FMT types for immunohistochemical analyses, revealing unusual histological characteristics. A set of three malignant tumors exhibited an epithelial/myoepithelial population, with consistent myoepithelial immunohistochemical signatures. All Grade I malignant tumors resulted in subjects surviving one-year post-diagnosis. Morphologically, we propose categorizing them as feline ductal/canalicular adenoma/carcinoma and feline intracanalicular papillary adenoma/carcinoma, respectively. These findings contribute novel insights to FMT classification and are valuable for prognostic studies.